Suppression of KV7/KCNQ potassium channel enhances neuronal differentiation of PC12 cells. (1st October 2016) - Zhou, Najing; Huang, Sha; Li, Li; Huang, Dongyang; Yan, Yunli; Du, Xiaona; Zhang, Hailin
Graphical abstract: Highlights: KCNQ2/KCNQ3 K + channels are involved in neuronal differentiation, inhibition of these channels promote the neurite growth. The role of KCNQ2/KCNQ3 in neuronal differentiation is related to their action on cell membrane potential. T-type Ca 2+ channels contribute to the KCNQ-channel mediated neuronal differentiation. Abstract: Membrane potential shift driven by electrical activity is critical in determining the cell fate of proliferation or differentiation. As such, the ion channels that underlie the membrane electrical activity play an important role in cell proliferation/differentiation. KV 7/KCNQ potassium channels are critical in determining the resting membrane potentials in many neuronal cells. However, the role of these channels in cell differentiation is not well studied. In the present study, we used PC12 cells as well as primary cultured rat cortical neurons to study the role and mechanism of KV 7/KCNQ in neuronal differentiation. NGF induced PC12 cell differentiation into neuron-like cells with growth of neurites showing typical growth cone-like extensions. The Kv7/KCNQ blocker XE991 promoted NGF-induced neurite outgrowth, whereas Kv7/KCNQ opener retigabine (RTG) inhibited outgrowth. M-type Kv7 channels are likely involved in regulating neurite growth because overexpression of KCNQ2/Q3 inhibited neurite growth whereas suppression of KCNQ2/Q3 with shRNA promoted neurite growth. Membrane depolarization possibly underpins enhanced neurite growth induced by the suppression of Kv7/KCNQ. Additionally, high extracellular K + likely induced membrane depolarization and also promoted neurite growth. Finally, T-type Ca 2+ channels may be involved in membrane-depolarization-induced neurite growth. This study provides a new perspective for understanding neuronal differentiation as well as KV 7/KCNQ channel function.